A. `f(g(x))= ?`

Since f comes before g, to determine f(g(x)), we start with the function f(x).

`f(x) = 1/(2x-7)`

Then, replace the x with g(x).

`f(g(x))=1/(2(g(x))-7)`

Then, plug-in g(x)=x+6.

`f(g(x))=1/(2(x+6)-7)`

`f(g(x))=1/(2x+12-7)`

`f(g(x))=1/(2x+5)`

**Hence, `f(g(x))=1/(2x+5) ` .**

B. `(fof)(x)=?`

Since the letter that comes first is f, let's start with the function f(x).

`f(x) = 1/(2x-7)`

Since the letter after f is f too, replace the x in the function with f(x).

`f(f(x))=1/(2(f(x))-7)`

Then, plug-in f(x)=1/(2x-7).

`f(f(x))=1/(2(1/2x-7)-7)`

And, simplify.

`f(f(x))=1/(2/(2x-7)-7)`

`f(f(x))= 1/(2/(2x-7)-7) * (2x-7)/(2x-7)`

`f(f(x))=(2x-7)/(2-7(2x-7))`

`f(f(x))=(2x-7)/(2-14x+49)`

`f(f(x))=(2x-7)/(51-14x)`

**Hence, `(fof)(x)=(2x-7)/(51-14x)` .**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now